Recent Advances in the High‐Valent Cobalt‐Catalyzed C−H Functionalization of N‐Heterocycles. Issue 3 (21st December 2021) - Chandra, Devesh; Manisha,; Sharma, Upendra
Abstract: Direct functionalization of heterocycles using C−H activation widely relies on the precious metal complexes. In past decade, the use of earth abundant and inexpensive transition metal to functionalize heterocycles has become an attractive alternate strategy. This concept is also interesting due to the unique reactivity pattern of these inexpensive metals. In this context we and other research groups have utilized the high‐valent cobalt complexes as an inexpensive and readily available catalyst for the functionalization of heterocycles. In this review, we intend to brief recent progress made in the area of high‐valent cobalt complexes catalyzed C−H functionalization of N ‐containing heterocycles. Abstract : Direct functionalization of N ‐heterocyclic compounds holds great potential for the streamlined synthesis for complex molecules. High valent cobalt catalysts were found to be inexpensive alternative to their congener transition metal catalyst. The review summarizes the recent advancements in the field of high valent cobalt catalyst for the selective functionalization of N ‐heterocyclic compounds which are of prime importance in the field of organic chemistry.